Continuous and intermittent ketogenic diets initiated in late middle‐aged mice improves cognition and motor endurance at advanced age. (December 2021) - Zhou, Zeyu; Ramsey, Jon J; Long, Michelle; Wang, Regina; Kim, Kyoungmi; Graham, James; Rutkowsky, Jennifer
Abstract: Background: Alzheimer's disease (AD) is the most common age‐related neurodegenerative disease, and an effective therapeutic strategy that promotes healthy aging may lower age‐related risks of AD and ameliorate AD associated cognitive dysfunctions. There has been substantial interest in the application of ketogenic diets (KD) to manage neurological disorders associated with aging, and studies have also shown KDs started from early middle age improved cognition and longevity in mice. Thus, KDs might be used to reduce risk of cognitive declines at old age. KDs started later in life or intermittently administered may be more feasible and promote compliance in an older population. Therefore, this study sought to test if continuous or intermittent KDs started in late‐middle‐aged mice would improve measures of cognitive and motor function at advanced ages. Method: 18‐month‐old male C57BL/6J mice were randomly assigned to an isocaloric control (CD), ketogenic (KD), or intermittent ketogenic (IKD, 3 days of KD/week) diet. Continuous or intermittent ketosis was induced at a constant level of energy intake. At 20, 23, and 26 months of age, a panel of behavior tests were performed to assess cognitive (novel object recognition, Y‐maze, and Barnes‐maze) and motor (grid‐wire hang, grip strength, open field, and rearing) functions. Result: Y‐maze alternation rate was significantly higher for both IKD and KD mice at 23 months of age and for KD mice at 26 months indicating an improved working memory. 26‐month‐old KD mice also showed better spatial learning memory as measured by time spent in target quadrant in Barnes‐maze. Improved motor endurance and strength was observed in aged IK and KD mice as tested by grid wire hang. A significantly increased composite score of all the behavior parameters was observed in KD mice at 26 months of age, and IK mice showed a trend toward increased score compared to CD mice. Conclusion: KD and IKD initiated in late‐middle‐aged mice improved cognition and motor endurance in aged mice. KD had a more potent effect on overall heath span in aged mice shown as a higher composite score of all the tests performed with IKD showing results intermediate to other diet groups.